PERFORMANCE OF GRAIN QUALITY AND AROMA OF AROMATIC NEW PLANT TYPE PROMISING RICE LINES - Lestari, Angelita Puji; Abdullah, Buang; Junaedi, Ahmad; Aswidinnoor, Hajrial (Indonesian Agency for Agricultural Research and Development - MOA, 2011)
Grain quality and aroma are important characteristics of rice that affect consumer acceptance. This research was conducted to study the grain quality and aroma of aromatic new plant type (NPT) promising rice lines. Thirty five lines as well as Ciherang and Sintanur varieties were planted at Bogor and Pusakanagara, West Java in the dry season (DS) 2009 and wet season (WS) 2009. Three methods, i.e. leaf aroma tested with KOH, rice aroma tested in the test tube, and cooked rice aroma test, were used to evaluate the aroma of the lines. The results showed that line B11742-RS*2-3-MR-34-1-2-1 was aromatic identified using different methods. The line had long, slender, and small chalkiness grains, high percentage of head rice, high amylose, and hard texture. Lines IPB 140-F-6, B11249-9C-PN-3-3-2-2-MR-1, and B11955-MR-84-1-4 also had a high aroma score and grain yield. Testing leaf aroma with KOH can be used as early selection method in breeding program for aromatic lines. Lines derived from aromatic parents from highlands of South Sulawesi did not show consistent aroma under three testing methods. Those tested lines had good grain quality, both physical and cooked rice quality.